Formação de professores para educação inclusiva na rede municipal de ensino de Floriano/PI - Paiva Neta, Raimunda Ferreira (2014)
This paper is a study of the training of teachers for inclusive education in the Municipal Network of Education of Floriano/PI, focusing on the intellectually deficient student, the school, the pedagogical practices of the teachers in regular education and the Atendimento Educacional Especializado AEE [Specialized Educational Services], in light of the inclusive principles. In the first part, an analysis is carried out based on documents of civil society which provide the foundations for the Inclusive Policy, beginning with the Brazilian Magna Carta that is, the Constitution of the Federal Republic, the presidential resolutions and decrees, guaranteeing the permanence of children with intellectual deficiencies in the class room, the right to accessibility to education and study in a quality school; the impact of the Inclusive Education Program in the Municipality of Floriano, the implementation of the inclusive policy, the advances and regressions, having as a referential marking point the process of inclusion in education. In the second part teacher training is dealt with, both to enable mediation of the teaching in a regular classroom, as well as to put into operation the AEE in a Multifunctional Resource classroom. Many writers and specialists and researchers on the issue of intellectual deficiency in the training of teachers were consulted, studied for the formulation of the theoretical reference. The third part of the study is a social research carried out in loco with five teachers of five municipal schools which have students with intellectual deficiency enrolled in the regular classrooms and in the AEE. The listening was materialized through a qualitative questionnaire of thirteen open questions, investigating the putting into practice of the inclusion policy, the training of the teacher of regular teaching and of AEE and the inclusive practices, based on the direct contact with the students with intellectual deficiency ID. The proposal does not intend to give a recipe for the training of teachers for inclusive education. Instead, it is to be an opening of possibilities for those who are involved with the training, the teachers themselves, the administrators, the family members and the school community to perceive themselves as agents and not as mere receivers of legal determinations.